The Impact of an Introductory Biomedical Engineering Course on Students' Perceptions of the Engineering Profession - Quiroga Torres, Daniel Alejandro; Florez Luna, Nestor; Rodríguez Dueñas, William Ricardo; Rios Rincon, Adriana; Cruz, Antonio Miguel (Tempus Publications, 2016)
After their ﬁrst year roughly 50% of engineering students do not continue in that major. One cause could be that students have little idea as to what the profession of engineeringis about. Freshman introductory courses provide a ﬁrst approach to the engineering profession. Therefore, understanding the role of introductory engineering courses to increasing student knowledge of the profession is a relevant issue. The purpose of the study is to describe how student perceptions of the engineering profession overall change as a result of their educational experience in an introductory biomedical engineering course.This is a pre-post-test with no control group study design.One class(n =41)on a ﬁrst-year biomedical engineering course participated in a hybrid Project-based-learning (PBL)-lecture learning strategy. A survey composed of a demographic and 5-point Likert (‘‘1’’ is strongly disagree and ‘‘5’’ is strongly agree) sections measured students’ perceptions of the engineering profession and was administered (paper-based) to all the students enrolled on this course. The students’ perceptions of the engineering profession were pooled into 3 main groups of skills, i.e. Technical skills, Professional skills, and Project management skills. Wilcoxon signed-rank test statistics were conducted to analyze the research question. Our analysis showed statistically signiﬁcant results (pre-survey mean and SD: 4.01, 0.07; and post-survey mean and SD: 4.21, 0.05, p < 0.003), indicating the students’ overall perceptions of the engineering profession had signiﬁcantly improved by the end of the course. The results indicated that the students’ overall perceptions of the engineering profession had signiﬁcantly improved by the end of the introductory course.

Después de su primer año, aproximadamente el 50% de los estudiantes de ingeniería no continúan en esa carrera. Una causa podría ser que los estudiantes tengan poca idea de lo que es la profesión de ingeniería. Los cursos introductorios para estudiantes de primer año brindan un primer acercamiento a la profesión de ingeniería. Por lo tanto, comprender el papel de los cursos de introducción a la ingeniería para aumentar el conocimiento de los estudiantes sobre la profesión es un tema relevante. El propósito del estudio es describir cómo las percepciones de los estudiantes sobre la profesión de ingeniería cambian en general como resultado de su experiencia educativa en un curso introductorio de ingeniería biomédica. Esta es una prueba previa y posterior sin diseño de estudio de grupo de control. Una clase (n =41) en un curso de primer año de ingeniería biomédica participó en una estrategia híbrida de aprendizaje basado en proyectos (PBL)-lectura. Una encuesta compuesta por secciones demográficas y Likert de 5 puntos ('1' es muy en desacuerdo y '5' es muy de acuerdo) midió las percepciones de los estudiantes sobre la profesión de ingeniería y se administró (en papel) a todos los alumnos matriculados en este curso. Las percepciones de los estudiantes sobre la profesión de ingeniería se agruparon en 3 grupos principales de habilidades, es decir, habilidades técnicas, habilidades profesionales y habilidades de gestión de proyectos. Se realizaron pruebas de rango con signo de Wilcoxon para analizar la pregunta de investigación. Nuestro análisis mostró resultados estadísticamente significativos (media y desviación estándar antes de la encuesta: 4,01, 0,07; y media y desviación estándar después de la encuesta: 4,21, 0,05, p < 0,003), lo que indica que las percepciones generales de los estudiantes sobre la profesión de ingeniería habían mejorado significativamente con el final del curso. Los resultados indicaron que las percepciones generales de los estudiantes sobre la profesión de ingeniería habían mejorado significativamente al final del curso introductorio.
Keywords: Educación Superior -Universidades; Ingeniería Biomédica; Biomedical engineering; Escuela Colombiana de Ingeniería Julio Garavito - Estudiantes; Pedagogía de la ingeniería; Engineering pedagogy; Educación; Ingeniería; Education; Engineering